Livestock farmers’ vulnerability to climate change in the extreme northern region of Benin Republic - Amoussou, Jessika P.; Dossa, Luc Hippolyte; Adewumi, Matthew O. (My University, 2017)
Evidence from the Intergovernmental Panel on Climate Change is now overwhelmingly convincing that climate change is real and its negative impacts are more severely felt by poor people in developing countries who rely heavily on the natural resource base for their livelihoods. Animal husbandry is a major activity among the most climate-sensitive economic sectors, but very little is known about the vulnerability level of livestock farmers to climate change in the extreme northern region of Benin Republic. This motivated this work which aimed to assess the effect of climate change on livestock production in the localities of Karimama and Malanville by developing a vulnerability index. A total of 221 ruminant households were surveyed between April and May 2017. The integrated assessment approach was used to quantify the vulnerability through a composite index comprised of sub-indices related to exposure, sensitivity and adaptive capacity of pastoral communities. The findings from this research work showed that the commune of Malanville is more vulnerable to climate change than Karimama despite the fact that they were exposed at the same level. Results also show that exposure, sensitivity and adaptive capacity differently influenced the vulnerability of livestock farmers. Also, socioeconomic features influenced the level of vulnerability. In practical terms, the study showed that efforts to reduce vulnerability must be integrated to act simultaneously on exposure, sensitivity and adaptive capacity. In addition, it will support pastoralist communities to diversify their livelihoods. Finally, special attention should be given to systems of collection and provision of data and information for research.
Keywords: Bovins; changement climatique; éleveurs; indice de vulnérabilité.